An exploration of the mechanisms of health literacy and psychological empowerment influencing chronic disease patient health behaviours in Kuwait - Alwadaany, Bader M.S.H. (2019)
Chronic disease and its patients make up a significant proportion of Kuwait's health problems; this population is at high risk for morbidity and mortality if behavioural interventions don’t become part of the management of chronic disease.